3+2x+6=-53

Simple and best practice solution for 3+2x+6=-53 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+2x+6=-53 equation:


Simplifying
3 + 2x + 6 = -53

Reorder the terms:
3 + 6 + 2x = -53

Combine like terms: 3 + 6 = 9
9 + 2x = -53

Solving
9 + 2x = -53

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 2x = -53 + -9

Combine like terms: 9 + -9 = 0
0 + 2x = -53 + -9
2x = -53 + -9

Combine like terms: -53 + -9 = -62
2x = -62

Divide each side by '2'.
x = -31

Simplifying
x = -31

See similar equations:

| 5x-11= | | 3-x=-1 | | -(-2+4x)-(3-4x)+5=-(-3+6x)+x+1 | | -29+56= | | -4x-1+5x=-13 | | j/20=3 | | 3(x+8)=3x+24 | | x/4+2=-2 | | 22=6+2x | | k+4/2=k+9/2 | | (5x+4)(x-1)=2 | | k+4/2=k+9/4 | | -7x+2+4x=2 | | 40=12x+4 | | 2x-x+3+3x=x+13 | | -7x+2+5x=2 | | 6x^2+5x=-1 | | (2x-5)/3=(2-5x)/7 | | 22+x=12 | | 4(2x-8)=1/7(49x+70) | | 37g^8-37h^8= | | 19+x=2 | | x+x+16+3x=211 | | x^3+4x^2=7x+28 | | 1+2x+2x=49 | | 733=P(1+0.01)3 | | A=P(1+r)N | | 1/3x-15=18 | | 22=6f-8 | | -6=-1 | | -30+7x=26+3x | | 1-x=2(0,5-0,5x) |

Equations solver categories